(untitled) - Bassett, Jennifer (Oxford, 2008)
This award-winning collection of adapted classic literature and original stories develops reading skills for low-beginning through advanced students.
Keywords: English language,Reading comprehension,Đọc hiểu; Textbooks for foreign speakers.,Problems, exercises, etc.,Câu hỏi và bài tập